The Large-Firm Wage Premium in Developing Economies - Reed, Tristan; Tran, Trang Thu (World Bank, Washington, DC, 2019)
Large firms pay higher wages. In developing economies, the large-firm wage premium is comparable to the average gap between male and female wages, or two-thirds of the gap between urban and rural wages. There is substantial variation across countries in the share of the premium that is explained by sorting of human capital into large firms. The average large-firm wage premium declines in national income and has declined over time. Across industries, it is highest in public utilities and commerce. These stylized facts suggest several hypotheses about differences between labor markets in developing and advanced economies.